A new Zeno-free event-triggered scheme for robust distributed optimal coordination. (July 2021) - Yu, Hao; Chen, Tongwen
Abstract: This paper studies an event-triggered distributed optimal coordination problem for heterogeneous linear multi-agent systems with external disturbances. A new distributed optimal coordination algorithm based on event-triggered communication is proposed to deal with heterogeneous agents having a relative degree two. By utilizing the input-to-state stability guaranteed by the proposed algorithm, a novel distributed event-triggering condition is designed. It is showed that the robust distributed optimal coordination problem can be solved practically without Zeno behavior. Moreover, the relationship between the parameters in event-triggering conditions and the system performance is also studied. Finally, numerical simulations are provided to illustrate the effectiveness of the theoretical results.